Coherence in Thought and Action of the Indonesian Da'wah Mathla'ul Anwar Organization - Azima, Farhan; Andari, An; Ansori, Afif (JASNA : Journal For Aswaja Studies, 2024)
The coherence of ideas and actions concerning the Da'wah of the Mathla'ul Anwar organization in Indonesia is the subject of this article. As one of the biggest Islamic community organizations (ormas) in Indonesia following Muhammadiyah and Nahdlatul Ulama during the period of Indonesian independence, Mathla'ul Anwar (MA) worked with the Islamic modernization movement to encourage a spirit of struggle among the populace in order to avoid being impacted by the imperialists' exploitation, particularly in the Banten region. Up until now, MA organizations have adhered to all of the organization's rules, which include emphasizing social activities, education, and da'wah. The MA blends the pesantren and madrasa systems, with the latter's goal being the production of morally upright and well-rounded professional preachers. Up until now, the MA has the The institution of Mubaligh Mathla'ul Anwar, which houses young da'I cadres, is being developed with the organizational purpose of emphasizing amar ma'ruf nahi munkar. Though Khittah Mathla'ul Anwar lost the coherence of its organizational underpinnings during the New Order era, it remains a neutral Islamic community organization that does not adhere to political problems. The Supreme Court oversaw the Wattabligh fatwa assembly's operations and took part in the training of upcoming Indonesian da'I cadres. The author processes descriptive data using a technique that includes a literature review procedure. The idea of consistent MA along the fundamental lines of becoming a mass organization and a da'wah movement in society serves as the foundation for this study.